The method of multi objective synthesis of nonlinear robust control by multimass electromechanical systems - Kuznetsov, B. I.; Nikitina, T. B.; Bovdui, I. V.; Voloshko, O. V.; Kolomiets, V. V.; Kobilyanskiy, B. B. (Національний технічний університет "Харківський політехнічний інститут", 2022)
Development of the method of multi objective synthesis of nonlinear robust control by multimass electromechanical systems to satisfy various requirements for the operation of multi-mass systems in various modes. Methodology. The problem of multi objective synthesis of nonlinear robust control of multimass electromechanical systems is formulated and the possibility of satisfying various requirements for the operation of such systems in various modes based on the concept of functionally multiple membership of the state vector and the solution of the Hamilton-Jacobi-Isaacs equation is shown. A method for choosing weight matrices with the help the vector of purpose of nonlinear robust control is formed by solving a zero-sum vector antagonistic game has been substantiated and developed. Results. The results multi objective synthesis of nonlinear robust two-mass electromechanical servo systems in which differences requirements for the operation of such systems in various modes were satisfied are given. Based on the results of modeling and experimental studies it is established, that with the help of synthesized robust nonlinear controllers, it is possible to improve of quality indicators of two-mass electromechanical servo system in comparison with the system with standard regulators. Originality. For the first time the method of multi objective synthesis of nonlinear robust control by multimass electromechanical systems to satisfy various requirements for the operation of multimass systems in various modes is developed. Practical value. From the point of view of the practical implementation the possibility of solving the problem of multi objective synthesis of nonlinear robust control systems to satisfy various requirements for the operation of multimass electromechanical systems in various modes is shown.

Розробка методу багатокритеріального синтезу нелінійного робастного керування багатомасовими електромеханічними системами для задоволення різноманітних вимог до роботи багатомасових систем у різних режимах. Методологія. Сформульовано задачу багатокритеріального синтезу нелінійного робастного керування багатомасовими електромеханічними системами та показана можливість задоволення різноманітних вимог до роботи таких систем у різних режимах на основі концепції функціонально множинної належності вектора стану та рішення рівняння Гамільтона-Якобі-Айзекса. Обґрунтовано та розроблено метод вибору вагових матриць, за допомогою яких формується вектор мети нелінійного робастного керування, шляхом розв’язання векторної антагоністичної гри з нульовою сумою. Результати. Наведено результати багатокритеріального синтезу нелінійних робастних двомасових електромеханічних сервосистем керування, в яких були задоволені різноманітні вимоги до роботи таких систем у різних режимах. На основі результатів моделювання та експериментальних досліджень встановлено, що за допомогою синтезованих нелінійних робастних регуляторів можна підвищити якісні показники двомасової електромеханічної сервосистеми в порівнянні з системою зі стандартними регуляторами. Оригінальність. Вперше розроблено метод багатокритеріального синтезу нелінійного робастного керування багатомасовими електромеханічними системами для задоволення різноманітних вимог до роботи багатомасових систем у різних режимах. Практичне значення. З точки зору практичної реалізації показана можливість вирішення задачі багатокритеріального синтезу нелінійних робастних електромеханічних систем керування для задоволення різноманітних вимог до роботи таких систем у різних режимах.
Keywords: multimass electromechanical systems; nonlinear robust control; multi objective synthesis; Hamilton-Jacobi-Isaacs equation; computer simulation; experimental research; багатомасові електромеханічні системи; нелінійне робастне керування; багатокритеріальний синтез; рівняння Гамільтона-Якобі-Айзекса; комп’ютерне моделювання; експериментальні дослідження